GAMBARAN GRIT PADA MAHASISWA PENDIDIKAN PROFESI DOKTER PERGURUAN TINGGI NEGERI (PTN) DAN PERGURUAN TINGGI SWASTA DI INDONESIA - Anisa Muharrani Salima; Margaretha Purwanti; Aireen Rhammy Kinara Aisyah (Atma Jaya Catholic University of Indonesia, 2024)
Medical professional students have responsibilities, such as facing unpredictable real situations, large numbers of patients, uncooperative patients, and difficulties with the diseases they treat. The number of responsibilities can cause emotional exhaustion, stress, and burnout for medical students. To overcome this, medical students need a “Grit”. Grit is the desire of oneself to achieve long-term goals accompanied by high perseverance and consistency of interest in these goals. This study uses a quantitative approach with a descriptive research design. The population of this study were medical professional education students in Indonesia. This study used a non-probability sampling technique with convenience sampling. The sample size used was 120 participants. The results of this study are professional medical education students have a high grit score (91.67%). Based on the dimensions of consistency of interest and perseverance of effort, the majority of medical professional students have high scores on both dimensions. In this study, the most selected internal factor was